Extracurricular Musical Creative Activity of Primary School Pupils Attending Mountain Schools in the Carpathian Region - Lypa, Iryna (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The essence of the declared idea of general music education for pupils based on Ukrainian national culture lies in the relation to music art as to an integral part of the spiritual life of people, appealing to folk music in the light of its connections with spiritual, material and practical world of a human being. To implement such an idea, it is necessary to put ethnoregional material widely into music educational practice at comprehensive secondary school. It is both an important component of ethnic and cultural environment of the child and the background for musical creative development. However, due to the music program for grades 1- 4 it is expected to use only 10% of ethnoregional material at the lesson 4. Therefore, the problem of organizing extracurricular musical creative activity for pupils based on ethnic culture of an appropriate region in Ukraine, especially a Carpathian one, is a burning question.